Person-oriented Leadership Enhancing Employee Outcomes - Alvianny Voo Nyuk Chong @ Albertus; Umi Hamidaton Mohd Soffian Lee; Azman Ismail; Zaleha Yazid; Nursaadatun Nisak Ahmad (Institut Perakaunan Negara, Jabatan Akauntan Negara Malaysia, 2024)
This study evaluates the relationship between person-oriented leadership and employee outcomes. Person-oriented leadership requires leaders to build and maintain their relation with the employees. In order to accomplish organizational goals, the leader need to understand that having a strong bond with the employee is important. Therefore this research focuses on the effect of person-oriented leadership on employee outcome. The data collection was conducted by distributing questionnaires to 200 employees in different divisions and departments at a public research university in Malaysia. The result of the SmartPLS path analysis model displayed four findings: first, participative leadership style was significantly associated with job satisfaction. Second, consultative leadership style was significantly associated with job satisfaction. Third, participative leadership style was significantly associated with organizational commitment. Fourth, consultative leadership style was significantly associated with organizational commitment. These findings demonstrate that it is important for leaders to implement participative and consultative leadership style during their day-to-day job operations, in order to ensure job satisfaction and organizational commitment of employees in organization.